The Influence Of Motivation And Organizational Culture On Psychological Well-Being Mediated By Employee Job Satisfaction: Systematic Literature Review (SLR) With Bibliometrics - Agus Rahmat Santoso; Budi Eko Soetjipto; Ludi Wishnu Wardhana; Madziatul Churiyah (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze and map the development of scientific studies on the influence of motivation and organizational culture on the psychological well-being of employees with job satisfaction as a mediating variable through the Systematic Literature Review (SLR) approach combined with bibliometric analysis. The research method uses an SLR approach with the stages of identification, selection, feasibility, and inclusion of articles obtained from various reputable scientific databases. The articles analyzed are international and national journal publications that are relevant to the topics of work motivation, organizational culture, job satisfaction, and employee psychological well-being. Bibliometric analysis was carried out to identify research trends, publication developments, author collaborations, as well as keyword mapping that is often used in related research. The results show that work motivation and organizational culture play an important role in increasing employee job satisfaction, which ultimately contributes to improved psychological well-being in the workplace. Job satisfaction has been shown to function as a mediating variable that strengthens the relationship between organizational factors and employee psychological conditions. In addition, the results of bibliometric analysis show that research on employee psychological well-being has been growing in recent years with a focus on aspects of a healthy work environment, organizational support, and strategies to improve the quality of work life. The findings of this study provide theoretical and practical implications for the development of human resource management in creating a conducive work environment, increasing employee motivation, and building a positive organizational culture to support the psychological well-being of employees in a sustainable manner.